The history of UiTM Sarawak / Ajurah Hailah ...[et al.] - Hailah, Ajurah; Sikau, Ann Nickline; Wasilie, Nurul Ain; Sid, Rostella (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2023)
In 1956, UiTM was established as Dewan Latehan RIDA (also known as Pusat Latihan RIDA), or the Rural and Industrial Development Authority (RIDA) Training Centre. Pusat Latihan RIDA first began operations in November 1956. Following that, in 1965, the role of Pusat Latihan RIDA was expanded, and the training centre became known as Maktab MARA or MARA College, and it was included into the Majlis Amanah Rakyat (MARA) Training Department. Later in 1967, in response to the need for more trained Bumiputera professionals, Maktab MARA has been upgraded to a tertiary institution and renamed Institut Teknologi MARA (ITM).